2021
DOI: 10.1002/cmdc.202100252
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐Aided Search for 5‐Arylideneimidazolone Anticancer Agents Able To Overcome ABCB1‐Based Multidrug Resistance

Abstract: Supporting information for this article is given via a link at the end of the document.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
(190 reference statements)
1
8
0
Order By: Relevance
“…Our ligand-based pharmacophore model postulated one hydrogen bond acceptor (HBA), three hydrophobic groups (Hyd1, Hyd2, and Hyd3), and one aromatic (Aro) feature for the selection of highly potent inhibitors of ABCB1. Previous efforts to develop pharmacophore models for ABCB1 inhibition consistently identified the presence of hydrophobic groups and hydrogen-bond acceptors as essential features [ 13 , 26 , 42 ]. However, the distance matrices varied slightly from our results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our ligand-based pharmacophore model postulated one hydrogen bond acceptor (HBA), three hydrophobic groups (Hyd1, Hyd2, and Hyd3), and one aromatic (Aro) feature for the selection of highly potent inhibitors of ABCB1. Previous efforts to develop pharmacophore models for ABCB1 inhibition consistently identified the presence of hydrophobic groups and hydrogen-bond acceptors as essential features [ 13 , 26 , 42 ]. However, the distance matrices varied slightly from our results.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [ 42 ] developed a pharmacophore model on the basis of 16 compounds, and reported three hydrophobic groups and one hydrogen bond acceptor as the crucial pharmacophoric features. Similarly, Ilza et al [ 26 ] delineated three hydrophobic groups and a hydrogen bond acceptor as the important features on the basis of aligning three active compounds, while Kaczor et al [ 13 ] used a dataset of 17 arylideneimidazolone derivatives including five active inhibitors and twelve inactive compounds to identify the importance of an aromatic group and hydrogen bond acceptor. Our pharmacophore model included all of the aforementioned features because we used a diverse dataset of 98 compounds that were described as selective for ABCB1 and that we were able to dock into a molecular model based on structure data for the human transporter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These alkylating reagents have an important role in the construction of a series of C–S bonds (Scheme ). Taking classical methylation as an example, methylation of thioureas has traditionally been carried out using unstable, volatile, or toxic methylating agents . Alternatively, sulfuric esters can be used as an alkylation source as well, but they are generally highly toxic and explosive .…”
Section: Introductionmentioning
confidence: 99%